Nepal : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report, 2006)
This Selected Issues paper examines the effect of political instability on economic growth in Nepal. It uses publicly available data on political economy variables for 167 countries worldwide from 1970-2004 to estimate the impact of political instability on growth. The findings reveal that Nepal has witnessed higher political instability compared with other countries in the region. The paper also presents the salient features of political instability and growth for Nepal and other South Asian countries, and the econometric estimates of growth regressions to measure the effect of political instability on economic growth.